Corrupting luxury in ancient Greek literature - Gorman, Robert (Robert Joseph); Gorman, Vanessa B., 1963- (University of Michigan Press, 2014)
Traces the principle that luxury corrupts its possessor as seen through a millennium of Greek literature.